Cyber Security 15th International Annual Conference, CNCERT 2018, Beijing, China, August 14-16, 2018, Revised Selected Papers - Yun, Xiaochun; Wen, Weiping; Lang, Bo; Yan, Hanbing; Ding, Li; Li, Jia; Zhou, Yu (Communications in Computer and Information Science, 2019)
This open access book constitutes the refereed proceedings of the 15th International Annual Conference on Cyber Security, CNCERT 2018, held in Beijing, China, in August 2018. The 14 full papers presented were carefully reviewed and selected from 53 submissions. The papers cover the following topics: emergency response, mobile internet security, IoT security, cloud security, threat intelligence analysis, vulnerability, artificial intelligence security, IPv6 risk research, cybersecurity policy and regulation research, big data analysis and industrial security.